Agent-Based Modeling for Efficiency Policy of Households' Electricity Consumption in Bandung City - Sari, Devilia; Putro, Utomo Sarjono (SBM ITB, 2011)
There are many argumentations that the government subsidy in electricity, for holding down the electricity fares, has encouraged extravagant use of electricity. Therefore, the Government Budget (APBN) Burden for this subsidy becomes higher than it necessary. Some experts have argued that this money can actually be used for other necessary and urgent spending such as infrastructure development. The purpose of this research is to build an agent-based model and simulation to explore the dinamic of electricity consumption in Indonesia, especially in Bandung City. Several interviews were conducted about households' behaviors in consuming electricity to build the model. Then, the parameter was set based on the data collected with questionaire and secondary data source. The model was tested for its validity and sensitivity to the change in the controlled parameter. The simulation is expected to provide the government with a combination of electricity fare to various households electricity market segments to ensure an economic use of electricity. Some scenarios were run and the emergent property, the whole system electricity consumption,were observed to find out the best policy to encourage efficient use of electricity in the system.Keywords: agent-based modeling, electricity consumption, electricity fare, households, simulation,electricity cost.